Assessment of Physicochemical Properties and Cooking Quality of Promising Rice Varieties - Naik, M. Vinod Kumar; Pillai, M. Arumugam; Saravanan, S. (International Journal of Bio-resource and Stress Management, 2023)
The study was carried out in AC and RI, killikulam, Tamil Nadu Agricultural University, Tamil Nadu, India during Kharif 2017 to evaluate physiochemical and cooking properties of promising high yielding rice varieties of Tamil Nadu. Different physiochemical properties were studied in Fifty-five rice varieties. The hulling percentage varied from IR 28 (88.85) to CO 39(62.5), milling percentage ranged between IR 28(79.6) to C0 39(59.35), HRR% varied from IR 28 (73.3) to CO 43 (42.5), grain length is highest in Pusa Basmati (8.85 mm) and lowest in short grain type TN 1 (4.05 mm), The grain breadth ranged between 1.5 mm (JGL 3855) – 2.4 mm (ASD 2). L/B ratio, varied from 5.72 (Pusa Basmati) to 1.84 (TN 1), grain length after cooking ranged from Pusa Basmati (14.7mm) to BRNS (WP) 5 (5.35mm). Whereas the highest grain breadth after cooking was observed in ASD 2 (4.75 mm) and the lowest observed in Pusa Basmati (2.05 mm), linear elongation ratio is ranged from 1.67 (Pusa Basmati) to 1.04 (TPS 3), breadth wise expansion ratio was varied from TPS 3(2.49) to Pusa Basmati (1.33), ASV recorded 4 , 7, 27,11 and 7 varieties for scale-2, scale-3,scale-4, scale-5, scale-6 respectively. gel consistency ranged from 99.55 mm (JGL 3855) to 55.5 mm (Swarna) and the amylose content varied from 39.45 (Abhya) to 13.55(ASD 17). The relationship between physicochemical and cooking properties was determined using Pearson’s correlation. Correlation was done for determining the nature of interaction among the characters.